A bibliometric review of the water security concept in Central Asia. (18th December 2020) - Xenarios, Stefanos; Assubayeva, Aliya; Xie, Lei; Sehring, Jenniver; Amirkhanov, Daulet; Sultanov, Alisher; Fazli, Siamac
Abstract: Engineering, economic, social sciences, geophysical, and integrated modeling studies have approached the assessment of water security in Central Asia (CA) in distinct ways. Different indicators and indexes have been introduced to assess the most vulnerable aspects of water use in this region. Until now, though, the suggested approaches are often represented in a fragmented manner, while the relevant indicators cannot fully attribute the vulnerability status of a country or on a regional level. This can result in diverging perceptions of the water security situation in policy dialogues, also affecting bilateral and multilateral relations among the countries in CA. In this study, we conduct a bibliometric review on the approaches and methods that directly or indirectly touch upon the water security perceptions in CA. We employ data mining techniques to explore trends in the conceptualization of water security in the region since the breakup of the Soviet Union by also identifying the water interests and priorities set by each country. The findings reveal that within the last decade, the water security-related studies have given much importance to technical and infrastructural means to protect human livelihoods against global environmental changes but also to foster economic growth. The water governance and management aspects are largely overlooked in favour of more techno-centric approaches. These findings are expected to clarify further the perception of the water security concept within CA by indicating the geophysical, institutional, and historical challenges that need to be met for a mutual understanding among the countries in the region.